Experimental research on CO2 inhibiting the spontaneous combustion of high sulfur coal - LAN Anchang, GUO Chunsheng, LI Yaoqian, ZHANG Jilin, BAI Gang, ZHOU Xihua, WANG Siqi (Meikuang Anquan, 2022)
In order to study the inhibitory characteristics of CO2 on the spontaneous combustion of high-sulfur coal, the high-sulfur anthracite from Yangquan was selected to conduct thermogravimetric analysis experiments under different ratios of φ(O2)/φ(CO2), exploring the influence of CO2 on the spontaneous combustion process of high-sulfur coal from the perspective of combustion characteristics, heat release and activation energy. The results show that with the increase of CO2 concentration, the temperature range of the three stages of high-sulfur coal combustion is “hysteresis”, and the heat release and the rate of heat release gradually decrease; the ignition temperature, combustion temperature and maximum weight loss temperature increase with the increase of CO2, which inhibits the combustion process of high-sulfur anthracite. In inert atmosphere, the combustability of high-sulfur coal decreases and the energy required for combustion increases. The inhibitive effect of CO2 on the spontaneous combustion of high sulfur anthracite was revealed from the decrease of combustion and exothermic property and the increase of activation energy.